Sistem Informasi Geografis Pemetaan Area Menggunakan Arcgis (Studi Kasus Lokasi Organisasi Masyarakat (Ormas) Keagamaan Di Kota Palembang) - Dwi Puji Rahmat; Darius Antoni; Heri Suroyo (Jurnal Nasional Ilmu Komputer, 2021)
The result of this research is a web-based WebGIS or Geographic Information System design using ArcGIS software, then input into ArcGIS online and system development using the Unified Process (UP). Geographic information system for mapping the area using Arcgis (Case Study of the Location of Religious Community Organizations in Palembang City) in its use, this Web-based GIS aims to facilitate various parties, especially KESBANGPOL Palembang City and KEMENAG Palembang in mapping the distribution of CSOs, especially in this case is Religious categories that have been registered and types the information. With the geographical information system mapping the location of religious organizations, it is hoped that it will be useful and assist in knowing the layout of the location and information for these organizations so that the delivery of information becomes more effective.